Reactions from Comparative Education to Post-Modernism: From Initial Ortodoxy to Creative Heterodoxy in a Globalized World - María Jesús Martínez Usarralde (Revista Electrónica de Investigación Educativa)
The aim of this article is to analyse the influence that the paradigm of Postmodernism exerts, as a reaction to Modernism, and what the consequences of all these are in a globalized world: the adoption of a reflective disposability in crescendo and an increased consciousness and openness to diverse perspectives, which lead to adopt a certain component of relativism, criticism and irony in education. With all this, the spectrum of "uncertainty" is growing, due to the continuous changes which are developing around it. As a consequence, two theoretical proposals emerge from Comparative Education, learnologies and transitologies, which contribute to a new vision of the discipline. While the first one interprets the incessant changes, which require new educational codes in order to understand the transformations of the world, the second one refers to the closest reality of the subject and the access to knowledge. To sum up, Comparative Education has found a new direction from both proposals, and it will probably lead to diverse Comparative Educations or a phase of Neo-comparative Education.